Personal mobile-health application - Lim, Jeremy Yeu Shuo (2025)
Nowadays in the society, there is a phenomenon for raising health awareness and encouraging healthier lifestyles with the growing use of mobile health apps. However, the issues have been discovered such as ineffectiveness in managing the risks of chronic diseases, low user engagement, and insufficient features for individualized health insights. Through the application of innovative technological approaches and a user centred design approach, this project aims to fill these gaps. The Android-based mobile health application will employ ML-driven algorithms to diagnose the risk of chronic diseases, giving users personalized early warnings and proactive health management tools. The proposed mobile health application will be considered about user engagement and motivation of using the application which provides user engagement features like chatbot as personal health assistant to increase user engagement and motivation by achieve healthy lifestyle practice. The proposed application will also be leveraging the device's camera, various of assessment, text-sentiment analysis and AI emotion recognition technology that will evaluate the user's emotions before offering personalised insights and practical guidance to enhance mental and emotional health well-being. The application will provide user-friendly interfaces that make it simple to access and use personalized health information, goal monitoring and health comparisons of themself. In order to create a secure, scalable, and highly user interactive that enables users to efficiently manage their general health, the solution will be created in an Agile environment using tools like TensorFlow Lite, Firebase, and Kotlin as the primary of programming language in this development.